Implementasi MYOB Accounting Versi 18 Dalam Pengolahan Data Akuntansi Pada Koperasi Karyawan Kampus Biru Sejahtera - Ngaijan, Ngaijan (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
The implementation of MYOB Accounting at the Blue Campus Prosperous Employee Cooperative is a strategic step to increase efficiency and accuracy in financial management. Previously, this cooperative used a manual system which was prone to errors and took time in the process of recording transactions. By switching to MYOB Accounting, cooperatives can automate various financial processes, from recording daily transactions to monthly financial reports. This implementation not only speeds up the administrative process, but also increases the transparency and accountability of financial reports. As a result, the Biru Sejahtera Campus Employee Cooperative has experienced an increase in data-based decision making, as well as making it easier for members to access financial information. It is hoped that the implementation of this software-based accounting system can become a model for other cooperatives in improving financial management professionally and efficiently.